Pengaruh Lingkungan Kerja, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Bagian Produksi PT. Njonja Meneer Semarang - Noeria Susitianigrum; Handoyo Djoko Waluyo; Reni Shinta Dewi (Universitas Diponegoro, 2015)
Every company needs a resource that has an important influence to achieve the expected goals. Resources may include natural resources, human resources, knowledge resources and technology resources. Employee performance is not good due to poor working environment, lack of motivation and lack of work discipline PT. Njonja Meneer Semarang engaged in the herbal industry in which there are production employees are actively involved in the company's production activities.This type of research is explanatory research. The sampling technique include nonprobability sampling technique is purposive sampling. The sample in this research were 76 respondents who are production employees of PT. Njonja Meneer Semarang. In the analysis of the test used factor analysis with SPSS 20.Results of statistical analysis known partial effect of the work environment on employee performance by 57,2%. Then the motivation on employee performance by 55,2%. As for the discipline of work on employee performance by 44,5%. Effect of Simultaneous influence of the working environment, motivation and discipline to the employee performance by 72,0%, while 28,0% are influenced by other factors.Recommendations for improving the performance of employees to the company to increase its attention to the work environment, motivation and discipline of work which in turn will ultimately increase employee performance.